2016
DOI: 10.1039/c5ra25880d
|View full text |Cite
|
Sign up to set email alerts
|

Generation of open-ended, worm-like and graphene-like structures from layered spherical carbon materials

Abstract: A study of the effects of size dispersion of Au@SiO 2 spheres and silica sphere templates for the synthesis of hollow carbon structures was evaluated using a chemical vapor deposition (CVD) nanocasting method. The diameter of the template, the presence of the gold nanoparticles and the polyvinylpyrrolidone (to cap the Au particles) were found to determine the size, thickness and shape of the synthesized carbon nanostructures. The Au@monodispersed small-sized silica sphere (80-110 nm) template covered with carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The SiO 2 spheres and the HCSs were synthesized based on a procedure described elsewhere. 50 The preparation of the HCSs and HCS/PVP solutions using a surfactant dispersion method is described in the ESI † section.…”
Section: Synthesis Of the Sio 2 Spheres And The Hcssmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiO 2 spheres and the HCSs were synthesized based on a procedure described elsewhere. 50 The preparation of the HCSs and HCS/PVP solutions using a surfactant dispersion method is described in the ESI † section.…”
Section: Synthesis Of the Sio 2 Spheres And The Hcssmentioning
confidence: 99%
“…S1 †). 50 The shell diameter in the pristine HCSs was approximately 18 AE 4 nm due to the use of a short (1 h) carbonization time. The TG-DTG curve of the HCSs shows a small derivative peak between 290 C and 400 C (Fig.…”
Section: Characterization Of the Hcssmentioning
confidence: 99%
“…The SiO2 spheres were synthesized following a modified procedure reported elsewhere 17 . Briefly, 180 mL of ethanol, 60 mL of distilled water and 10 mL of NH4OH were mixed in a volumetric flask and stirred for 30 min.…”
Section: Synthesis Of Sio2 Spheres and N-hcssmentioning
confidence: 99%
“…For instance, the carbon shell thickness that is formed on a template can be controlled by varying the surfactant to precursor ratio 13,14 , the amount of the carbon source 15 and the carbonization time 16 . A longer carbonization time and a larger amount of a carbon source result in the formation of a thicker carbon shell whereas a shorter carbonization time will yield a thinner carbon shell 17 . The change in the HCSs shell thickness can influence their degree of graphitization and the conductivity of the carbon layer 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in another study by Sevilla et al [ 18 ], they synthesized graphitic carbon structures using gluconate dehydrates of iron and cobalt, and reported that iron and cobalt nanoparticles successfully catalyzed the reaction at either 900 or 1000 °C. Different CNMs, i.e., worm-like and broken hollow carbon nanostructures, were synthesized using gold- and silica-containing precursors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%